PENGENALAN TEKNOLOGI PENGERINGAN CABAI UNTUK KELOMPOK TANI DI SEKARTAJI TABANAN - Kasmawan, I.G.A.; Sutapa, G. N.; Yuliara, I. M.; Ratini, N. N.; Baskoro, W. T.; Trisnawati, N. L. P. (Buletin Udayana Mengabdi; Vol 20 No 3 (2021): Buletin Udayana MengabdiDO - 10.24843/BUM.2021.v20.i03.p03, 2021)
The price of chili that falls when the harvest is abundant is certainly very detrimental to farmers. This needs to be addressed immediately by extending the shelf life of chili using appropriate technology through community service programs. The purpose of the program is to introduce chili drying techniques using a chili dryer. The method of implementing the service uses interactive lecture methods and practices about processing technology for raw chili products to become dry chili using a chili dryer. The result obtained is the creation of a simple chili dryer with gas fuel. The tool is built using a combination of metal (90%) and wood (10%) measuring 80 x 50 x 120 cm3, with a capacity of up to ± 7 kg of raw cayenne pepper. Red chili and green chili experienced weight loss of about 80% and 90%, respectively, with very contrasting product colors. The drying process with a dryer is faster (6 hours) than the conventional method (7-10 days). Based on the results of the questionnaire, the success rate of the implementation of the service program is above 90% Keywords: chili price, chili dryer, gas fuel, dry chili, weight loss